Development of the front end amplifier circuit for the ATLAS ITk silicon strip detector. (29th July 2021) - Cormier, K.J.R.; Gallop, B.; Kaplon, J.; Li, Z.; Noy, M.; Phillips, P.W.; Sawyer, C.A.; Sperlich, D.; Warren, M.
Abstract: We present the development of the front end amplifier circuit for the ABCStar readout ASIC designed for the upgraded ATLAS Inner Tracker (ITk) detector. The amplifier is intended to work with silicon strip sensors of moderate length between 1.9 cm and 5.5 cm dependent on position in the detector. The final circuit is implemented in a commercial 130 nm CMOS process tolerant up to the total ionizing doses (TID) predicted for the lifetime of the detector, that is maximum of 66 Mrad (660 kGy) (Si) for the endcap region. The final architecture and the performance of the circuit is presented in the context of a long development program which started soon after the construction of the present ATLAS Semi-Conductor Tracker (SCT) detector.